PENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA MELALUI PEMBELAJARAN GROUP INVESTIGATION SISWA KELAS VII C SMP N 1 NGLIPAR GUNUNGKIDUL - Andreas Ardya Eko; AA Sujadi (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of the study to describe the process of cooperative learning Group Investigation ( GI ) in order to increase motivation and learning mathematics class VII C SMP N 1 Nglipar Gunungkidul . This research was Classroom Action Research (CAR) conducted a minimum of two cycles. The subjects of this study were students of class VII C SMP N 1 Nglipar Gunungkidul totaling 32 students. The object of this study was motivation and learning outcomes of mathematics. The results showed that motivation and learning outcomes of mathematics has increased. Average percentage yield motivation questionnaire on pre cycle of 67.27 %, in the first cycle increased by 11.36 % to 78.64 %. In the second cycle increased by 6.57 % to 85.21 %. Initial ability to use the average value of the first half of the middle repeat is 59.84 with KKM attainment percentage of 13%. In the first cycle, the average increased 7.03 percentage points to 63.87 with KKM achievement by 53 %. In the second cycle an average increase of 6.22 percentage points to 73.09 with 63 % KKM achievement. Based on the results of the implementation of cooperative learning Group Investigation ( GI ) model can increased learning outcomes of matematics and motivation